2000
DOI: 10.1098/rstb.2000.0623
|View full text |Cite
|
Sign up to set email alerts
|

Trichome morphogenesis inArabidopsis

Abstract: Trichomes (plant hairs) in Arabidopsis thaliana are large non-secreting epidermal cells with a characteristic three-dimensional architecture. Because trichomes are easily accessible to a combination of genetic, cell biological and molecular methods they have become an ideal model system to study various aspects of plant cell morphogenesis. In this review we will summarize recent progress in the understanding of trichome morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…The most consistent vegetative phenotype of MPC RNAi plants was reduction of the number of branches on rosette leaf trichomes. Trichome branching is associated with endoreduplication of trichome nuclei (Schwab et al, 2000); one possibility is that loss of MPC function inhibits DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent vegetative phenotype of MPC RNAi plants was reduction of the number of branches on rosette leaf trichomes. Trichome branching is associated with endoreduplication of trichome nuclei (Schwab et al, 2000); one possibility is that loss of MPC function inhibits DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive studies on trichome development in Arabidopsis thaliana (e.g. Schwab et al 2000, Hu¨lskamp 2000, Szymanski et al 2000, Beilstein and Szymanski 2004 have identified a significant number of genes (e.g. ANGUSTIFOLIA, STICHEL, ZWICHEL) responsible for the genetic pathways that control trichome morphology.…”
Section: Charactersmentioning
confidence: 99%
“…The nonglandular trichomes are generally linear trichomes that lack secretory/storage cells at their tips (Schwab et al, 2000) and thus are not of interest for this investigation. The glandular trichomes of Solanum, on the other hand, first described by Luckwill (1943) and later reviewed extensively by Simmons and Gurr (2005), have been described as consisting of four distinct classes (types 1, 4, 6, and 7).…”
mentioning
confidence: 99%